2003
DOI: 10.1089/107999003321532501
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Interferons in Rotavirus Infections and Protection

Abstract: Type I and type II interferons (IFNs) play a critical role in control of a number of viral infections. To study whether altered and reduced functional capacities of type I and type II IFNs would affect rotavirus-induced diarrhea and viral replication, we obtained signal transducers and activators of transcription 1 (Stat1) knock-out mice (Stat1(-/-)) that lack many IFN-induced responses. We found that suckling Stat1(-/-) and immunocompetent mice orally infected with rotavirus experienced diarrhea and shed rota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
61
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 43 publications
5
61
0
Order By: Relevance
“…A similar response has also been reported with rotavirus infections in stat1 Ϫ/Ϫ mice, which are resistant to subsequent challenge (56 Ϫ/Ϫ mice are likely highly susceptible to nonvaccine strains of VACV (e.g., Copenhagen or Western Reserve strains). These data suggest that humans with mutations in stat1 could be contraindicated to vaccination with Dryvax and ACAM2000 and that following MVA vaccination, they may not receive the same level of protection as fully immunocompetent individuals.…”
Section: Discussionsupporting
confidence: 73%
“…A similar response has also been reported with rotavirus infections in stat1 Ϫ/Ϫ mice, which are resistant to subsequent challenge (56 Ϫ/Ϫ mice are likely highly susceptible to nonvaccine strains of VACV (e.g., Copenhagen or Western Reserve strains). These data suggest that humans with mutations in stat1 could be contraindicated to vaccination with Dryvax and ACAM2000 and that following MVA vaccination, they may not receive the same level of protection as fully immunocompetent individuals.…”
Section: Discussionsupporting
confidence: 73%
“…Using adult mice Zinkernagel and coworkers observed no significant effect of IFN-treatment on rotavirus induced diarrhoea and viral replication in these IFN-mutant mice (11)(12)(13). In this regard, age-related studies in mice, which were infected with rotavirus, revealed an age restriction of clinical symptoms (24,25) and therefore this data cannot be easily transferred to our model of infection of the newborn.…”
Section: Discussionmentioning
confidence: 95%
“…Cytokines measured in cell culture supernatants or through intracellular (34,39,40). Previously, elevated levels of both IL-6 and IFN-␥ were reported in studies with rotavirus-infected human patients (12,13,15,31).…”
Section: Discussionmentioning
confidence: 99%